Cerminan Konflik Batin : Perkembangan Identitas Pribumi dalam Film Bumi Manusia Berdasarkan Teori Vygotsky - Azizah Azizah; Retty Afrilia Gautami; Astri Carine; Wasilatul Bariroh (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The purpose of understanding Vygotsky’s theory is that we can apply the theory to the Bumi Manusia film or other films and films, we can gain a deeper understanding of this literary work. As well as benefits, Vygotsky’s theory provides us with a powerful tool to understand the complexity of character and social dynamics in the Bumi Manusia film. By looking at how social and cultural interactions shape the minds and identities of individuals, we can explore deeper meanings from this literary work. The research used in this study is a qualitative approach. A qualitative approach is a method that is often used and implemented by groups of researchers in the field of social sciences, including in various other fields of science. A qualitative approach is a research method through a process of understanding based on methods in investigating a phenomenon and a social problem. The data collection technique used in this study is the library or document technique. This technique marks each sentence or paragraph that is considered data, and groups the data and then analyzes it according to the formulation of the problem. The following are the steps for collecting data in this study, namely: reading the research data source, namely the Bumi Manusia film, marking the data in the form of sentence quotes, and collecting data that aims to classify the data according to the concept of genetic structuralism.